2012
DOI: 10.4040/jkan.2012.42.7.992
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rate and Factors Associated with Atopic Dermatitis among Korean Middle School Students

Abstract: Purpose: The purpose of this study was to verify prevalence rates of atopic dermatitis (AD) in middle school students in Korea and to define AD and associated factors. Methods: This study was conducted using secondary analysis of raw data from the 'The 6th Korean National Adolescent Health Behavior Survey, 2010' conducted by the Korea Centers for Disease Control. The participants were 37,570 students. General characteristics and health behavior-related characteristics were analyzed using descriptive statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The results of this study may be limited by its reliance on adolescent self-report; AD diagnosis was assessed based on response to a yes-or-no question written using wording from the ISAAC questionnaire. This study also found that prevalence of AD was 1.52-fold higher among female adolescents than among male students [ 6 ].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The results of this study may be limited by its reliance on adolescent self-report; AD diagnosis was assessed based on response to a yes-or-no question written using wording from the ISAAC questionnaire. This study also found that prevalence of AD was 1.52-fold higher among female adolescents than among male students [ 6 ].…”
Section: Resultsmentioning
confidence: 75%
“…AD prevalence among adolescents was assessed in a study using data from the Sixth Korean National Adolescent Health Behavior Survey, 2010, which was conducted by the Korea Center for Disease Control [ 6 ]. Of 37,570 adolescents who completed online self-report surveys, 22.6% reported an AD diagnosis within the past 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Burr et al ( 82 ) reported a 1-year prevalence lower than 10% for children, similar to Nissen et al ( 83 ), but higher prevalences were also reported and similar numbers reported for adults by Williams & Strachan ( 84 ). However, when considering the range of reported 1-year prevalence in the 21 st century, children showed the highest prevalence (22.6%) ( 28 , 36 , 81 84 ).…”
Section: Resultsmentioning
confidence: 96%
“…For children, the 1-year symptom prevalence ranged from 4.1% to 22.7% and for adults from 7.3% to 22.7% ( 28 , 42 , 43 ). The 1-year prevalence of doctor-diagnosed AD ranged from 1.2% in Asia to 17.1% in Europe in adults, and from 0.96% to 22.6% in children in Asia ( 1 , 32 , 34 36 ). For children, the lifetime symptom prevalence ranged from 4.4% to 17.7% assessed at age 7–15 years, and for adults ranged from 3.0% to 17.7% ( 28 , 31 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Stress can aggravate skin symptoms and thus further increase stress in patients with AE. This may lead to the maintenance and chronification of AE (9,10). In another study it was shown that receiving maternal welfare in comparison to not receiving social welfare was associated with a higher risk to develop asthma (Odds ratio = 1.87; (11)).…”
mentioning
confidence: 99%